2008
DOI: 10.4103/0970-0218.42047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental fluorosis among primary school children in rural areas of Chidambaram taluk, Cuddalore district, Tamil Nadu, India

Abstract: Background:Fluorosis is one of the common but major emerging areas of research in the tropics. It is considered endemic in 17 states of India. However, the Cuddalore district of Tamil Nadu is categorised as a fluorosis non-endemic area. But clinical cases of dental fluorosis were reported in the field practice area of Department of Community Medicine, Rajah Muthiah Medical College, Annamalai University, Chidambaram. Since dental fluorosis has been described as a biomarker of exposure to fluoride, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 6 publications
5
38
0
Order By: Relevance
“…Pipe water was the single most independent risk factor for dental fluorosis when association between water fluoride level and severity of dental fluorosis was considered for review. There was a positive association between dental fluorosis and source of water (P value< 0.05) Ninety five percent reported that they brushed their teeth only once,these findings were consistent with study done done by [15] The overall prevalence of dental fluorosis was found to be comparable with studies done by Saravanan S et al [10] and Mane AB et [15] . It was also observed that grade III and IV categories had caused discolouration of teeth,that is enamel hypoplasia probably occurred due to the consumption of water containing high level fluoride.…”
Section: Jmscr Vol||03||issue||08||page 6992-6996||august 2015supporting
confidence: 82%
See 1 more Smart Citation
“…Pipe water was the single most independent risk factor for dental fluorosis when association between water fluoride level and severity of dental fluorosis was considered for review. There was a positive association between dental fluorosis and source of water (P value< 0.05) Ninety five percent reported that they brushed their teeth only once,these findings were consistent with study done done by [15] The overall prevalence of dental fluorosis was found to be comparable with studies done by Saravanan S et al [10] and Mane AB et [15] . It was also observed that grade III and IV categories had caused discolouration of teeth,that is enamel hypoplasia probably occurred due to the consumption of water containing high level fluoride.…”
Section: Jmscr Vol||03||issue||08||page 6992-6996||august 2015supporting
confidence: 82%
“…Status of each patients was also recorded using decayed, missing & filled tooth (DMFT),enamel mottling and severity of dental fluorosis was recorded using Dean's Index on the WHO modified oral health assessment form. [7][8][9][10].…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…This is similar to the findings in rural areas of Udaipur i.e 36.36 percent and at Kerala (35.36 percent). On the other hand, a lower prevalence (12.52 percent) was recorded by Jain (1979) [4] at Naila and S Saravanan (2008) [5] at Tamil Nadu recorded 31.4 percent. This difference in the proportion may be due to the more use of toothpaste and tooth powder nowadays which may contaion fluorides to make foams.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of dental fl uorosis was more in 13-19 years age group (34.6%) followed by 6-12 years (23.6%) while prevalence was lower in >45 years age groups. Prevalence of skeletal fl uorosis was more common in above 45 years age group among both sexes while lower in the children (6)(7)(8)(9)(10)(11)(12). Prevalence of dental fl uorosis was more in the students (29.2%) whereas skeletal fl uorosis was the highest among farmers (35.1%).…”
Section: Resultsmentioning
confidence: 99%